My say: discuss the gold dinar issue objectively - Meera, Ahamed Kameel Mydin (The Edge Communications Sdn Bhd, 2009)
The world is reacting in many ways to the ongoing global economic crisis - quantitative easing, fiscal stimuli, currency swaps in trades, issuance of local currencies, opening gold markets and so on. The crisis is, unfortunately, still ongoing because the US, being a significant economy, is yet to recover from the crisis triggered by the collapse of its subprime mortgage market.